2015
DOI: 10.5194/acp-15-10669-2015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crustal dust and sea spray supermicron particle concentrations and acidity on inorganic NO<sub>3</sub><sup>−</sup> aerosol during the 2013 Southern Oxidant and Aerosol Study

Abstract: Abstract. Inorganic aerosol composition was measured in the southeastern United States, a region that exhibits high aerosol mass loading during the summer, as part of the 2013 Southern Oxidant and Aerosol Study (SOAS) campaign. Measurements using a Monitor for AeRosols and GAses (MARGA) revealed two periods of high aerosol nitrate (NO3−) concentrations during the campaign. These periods of high nitrate were correlated with increased concentrations of supermicron crustal and sea spray aerosol species, particula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 74 publications
5
90
0
Order By: Relevance
“…1 period, predicted R was on average 1.43 ± 0.32 for an ISORROPIA input with inferred Na + , 1.85 ± 0.17 for measured Na + input, and the highest R at 1.97 ± 0.02 when zero Na + was used as model input. The average measured R was 1.70 ± 0.23 by PILS-IC and 1.75 ± 0.20 by another PM2.5 water-soluble ion measurement (Allen et al, 2015). Thus, model R with measure Na + input was closest to the measured R. Under the meteorological conditions of the southeast in summertime (T = 25 ± 5 °C, RH = 68 ± 18 %), the thermodynamic model predicts R always near or equal to 40…”
Section: Nh4mentioning
confidence: 79%
“…1 period, predicted R was on average 1.43 ± 0.32 for an ISORROPIA input with inferred Na + , 1.85 ± 0.17 for measured Na + input, and the highest R at 1.97 ± 0.02 when zero Na + was used as model input. The average measured R was 1.70 ± 0.23 by PILS-IC and 1.75 ± 0.20 by another PM2.5 water-soluble ion measurement (Allen et al, 2015). Thus, model R with measure Na + input was closest to the measured R. Under the meteorological conditions of the southeast in summertime (T = 25 ± 5 °C, RH = 68 ± 18 %), the thermodynamic model predicts R always near or equal to 40…”
Section: Nh4mentioning
confidence: 79%
“…ALW in turn facilitates aerosol partitioning of HNO 3 . Field observations support HNO 3 uptake by aerosol waters during the daytime (Allen et al, 2015;Hodas et al, 2014). Notably, nitrate concentrations are strongly correlated with water-soluble organic compound concentrations (Hennigan et al, 2008b).…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 84%
“…The details of these monitoring sites including their longitudes and latitudes, NAPS monitoring station codes, and duration of the data record used for this study can be found in Table S1 in the Supplement. These sites were chosen because (1) they have long-term (at least 8-year) records of gaseous and PM 2.5 chemical components concentrations, and (2) they are located in the central region of North America with little influence of sea salt (Vet et al, 2014) and therefore the acidity of PM 2.5 is mainly dominated by the chemistry of sulfate, total nitrate and total ammonia (Young et al, 2013;Allen et al, 2015;Hennigan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%